2007
DOI: 10.1158/1078-0432.ccr-07-0747
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Profiling Identifies Afamin as a Potential Biomarker for Ovarian Cancer

Abstract: Purpose:To discover and validate serum glycoprotein biomarkers in ovarian cancer using proteomic-based approaches. Experimental Design: Serum samples from a ''discovery set''of 20 patients with ovarian cancer or benign ovarian cysts or healthy volunteers were compared by fluorescence two-dimensional differential in-gel electrophoresis and parallel lectin-based two-dimensional profiling.Validation of a candidate biomarker was carried out with Western blotting and immunoassay (n = 424). Results: Twenty-six prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
57
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(65 citation statements)
references
References 42 publications
6
57
2
Order By: Relevance
“…Despite the relatively small number of tissue and ascites specimens studied, the majority of proteins identified in the present study as being significantly differentially secreted from malignant and CTRL cell samples had been detected in previous studies (8)(9)(10)(11)(12)(13)(14)(15)(16), confirming their potent and important role. To the best of our knowledge, proteins including HSP-10 and DKK3, had not previously been identified by a proteomic approach, but had been suggested as potent markers using alternate approaches (19,30); however the present study was unable to confirm their utility as biomarkers of serous ovarian cancer by the immunological method.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Despite the relatively small number of tissue and ascites specimens studied, the majority of proteins identified in the present study as being significantly differentially secreted from malignant and CTRL cell samples had been detected in previous studies (8)(9)(10)(11)(12)(13)(14)(15)(16), confirming their potent and important role. To the best of our knowledge, proteins including HSP-10 and DKK3, had not previously been identified by a proteomic approach, but had been suggested as potent markers using alternate approaches (19,30); however the present study was unable to confirm their utility as biomarkers of serous ovarian cancer by the immunological method.…”
Section: Discussionsupporting
confidence: 76%
“…Certain previous studies have analyzed the proteomic profiles of ovarian tumor tissues, cell lines, urine, ascites fluid and blood samples (8)(9)(10)(11)(12)(13)(14). Analysis of the ovarian cancer cell line secretome has also provided information on potential markers (11,15).…”
Section: Introductionmentioning
confidence: 99%
“…35,36 Wu et al 37 reported that afamin was significantly down-regulated in hepatoma tissue. Jackson et al 38 showed that afamin was decreased in the serum of ovarian cancer patients. In contrast, we found that afamin was significantly elevated in the plasma of patients with SCC of the cervix.…”
Section: Discussionmentioning
confidence: 99%
“…ELP5 was initially identified as a component of a hyperphosphorylated RNA polymerase II (RNAPII) holoenzyme isolated from budding yeast chromatin and subsequently from human melanoma cells (26). AFM, one of the newest members of albumins, is considered a good prognosis marker in ovarian cancer (27)(28)(29). The mRNA expression levels of these genes were tested by qPCR to validate our microarray results.…”
Section: Lentivirus-mediated Sparc Overexpression By Skm-1 Cellsmentioning
confidence: 99%